Reversed phase HPLC determination of zidovudine in rat plasma and its pharmacokinetics after a single intranasal dose administration - Mainardes, Rubiana M.; Gremião, Maria Palmira Daflon [UNESP] (Soc Biolgia Chile, 2009)
The development and validation of a simple and accurate method based on HPLC with ultraviolet detection for the quantification of zidovudine in rat plasma and its application to a pharmacokinetic study following a single intranasal dose zidovudine is described. Zidovudine was extracted from the plasma using, a single-step deproteinization. Chromatographic separation of zidovudine from interfering components wits achieved with a C-18 reverse phase column, a mobile phase Consisting of a mixture of sodium acetate buffer (55 mM) with pH adjusted to 7.0 and acetonitrile (91: 9 v/v) and UV detection set at 265 run. The method was linear from 100 to 10000 ng.mL(-1) (r(2) >= 0.9995), and zidovudine had a mean recovery from plasma of 92.8%. The coefficient of variation of inter-day and intra-day quality control samples was less than 15%. After a single intranasal dose of zidovudine administered to rats, pharmacokinetic parameters (AUC(0-24), C(max), t(max), t(1/2)) were determined. The proposed method was found to be simple, specific. accurate, and precise and could be applied to the quantitative analysis of clinical pharmacokinetic studies of zidovudine in rats.
Keywords: RP-HPLC; validation; AZT; pharmacokinetics; intranasal delivery